2015
DOI: 10.2147/dddt.s76591
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the effect of lobeglitazone, a peroxisome proliferator-activated receptor-γ agonist, on the pharmacokinetics and pharmacodynamics of warfarin

Abstract: AimsLobeglitazone has been developed for the treatment of type 2 diabetes mellitus. This study was conducted to evaluate potential drug–drug interactions between lobeglitazone and warfarin, an anticoagulant with a narrow therapeutic index.MethodsIn this open-label, three-treatment, crossover study, 24 healthy male subjects were administered lobeglitazone (0.5 mg) for 1–12 days with warfarin (25 mg) on day 5 in one period. After a washout interval, subjects were administered warfarin (25 mg) alone in the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, the reduction in K p,liver for LB (i.e., from 2.34 to 1.55) by ATV did not appear to be significant in the total V ss , considering the fact that the contribution of the reduced distribution of LB to the liver would be approximately 27 ml/kg, which is relatively small for the V ss of 271 ml/kg. In other clinical DDI studies involving LB with metformin (i.e., T2DM agent), LB with warfarin (i.e., an anticoagulant with a narrow therapeutic index), or LB with amlodipine (i.e., an antihypertensive agent) (Shin et al, 2012;Jung et al, 2015;Kim et al, 2015), no apparent changes in the systemic pharmacokinetics was found. In contrast, however, the liver concentration of LB was significantly decreased by the coadministration of ATV ( Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the reduction in K p,liver for LB (i.e., from 2.34 to 1.55) by ATV did not appear to be significant in the total V ss , considering the fact that the contribution of the reduced distribution of LB to the liver would be approximately 27 ml/kg, which is relatively small for the V ss of 271 ml/kg. In other clinical DDI studies involving LB with metformin (i.e., T2DM agent), LB with warfarin (i.e., an anticoagulant with a narrow therapeutic index), or LB with amlodipine (i.e., an antihypertensive agent) (Shin et al, 2012;Jung et al, 2015;Kim et al, 2015), no apparent changes in the systemic pharmacokinetics was found. In contrast, however, the liver concentration of LB was significantly decreased by the coadministration of ATV ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that drug-drug interactions (DDIs) are possible for LB in drug metabolism as well as in its distribution to tissues. Clinical pharmacokinetics studies of LB with other prescription drugs such as warfarin or amlodipine were recently conducted in Korea, and no significant differences in the systemic pharmacokinetics of LB were reported after coadministration (Jung et al, 2015;Kim et al, 2015). These studies were designed to investigate potential changes in the systemic pharmacokinetics of LB when these drugs were coadministered, considering the fact that they are known to share some of the same metabolic pathways of LB (i.e., CYP1A2, CYP2C9, and CYP3A4 with warfarin; CYP3A4 with amlodipine) (Guengerich et al, 1991;Kaminsky and Zhang, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Exceptions were a slightly increased steady-state Cmax for sitagliptin (ratio, 1.1694; 90% CI, 1.0740 to 1.27320) and a slightly decreased Cmax for glimepiride (ratio, 0.910547; 90% CI, 0.78246 to 1.05960), when each was coadministered with lobeglitazone; however, neither of these changes were considered to be clinically significant [11,37]. There were also no significant changes in the pharmacokinetics of either drug when lobeglitazone was coadministered with amlodipine or warfarin [38,39]. However, coadministration with ketoconazole, a strong CYP3A4 inhibitor, increased the level of exposure to lobeglitazone by about 33% (geometric mean ratio for AUCinf, 1.33; 90% CI, 1.23 to 1.44) [40].…”
Section: Drug Interactionsmentioning
confidence: 99%
“…There were also no significant changes in the pharmacokinetics of either drug when lobeglitazone was coadministered with amlodipine or warfarin [ 38 , 39 ]. However, coadministration with ketoconazole, a strong CYP3A4 inhibitor, increased the level of exposure to lobeglitazone by about 33% (geometric mean ratio for AUC inf , 1.33; 90% CI, 1.23 to 1.44) [ 40 ].…”
Section: Lobeglitazone Characteristicsmentioning
confidence: 99%
“…Lobeglitazone is rapidly absorbed after oral administration, with a time to C max (T max ) of 1.0 to 3.0 hours, and is eliminated with a mean plasma elimination half‐life (t 1/2 ) of 7.8 to 9.8 hours in healthy subjects . Lobeglitazone was approved for the treatment of diabetes in 2013 by the Ministry of Food and Drug Safety, Republic of Korea …”
mentioning
confidence: 99%